Lovastatin Inhibits EMT and Metastasis of Triple-Negative Breast Cancer Stem Cells Through Dysregulation of Cytoskeleton-Associated Proteins - Zheng, Chanjuan; Yan, Shichao; Lu, Lu; Yao, Hui; He, Guangchun; Chen, Sisi; Li, Ying; Peng, Xiaojun; Cheng, Zhongyi; Wu, Mi; Zhang, Qiuting; Li, Guifei; et al. (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) is more aggressive and has poorer prognosis compared to other subtypes of breast cancer. Epithelial-to-mesenchymal transition (EMT) is a process in which epithelial cells transform into mesenchymal-like cells capable of migration, invasion, and metastasis. Recently, we have demonstrated that lovastatin, a 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitor and a lipid-lowering drug, could inhibit stemness properties of cancer stem cells (CSCs) derived from TNBC cell in vitro and in vivo. This study is aimed at investigating whether lovastatin inhibits TNBC CSCs by inhibiting EMT and suppressing metastasis and the mechanism involved. In the present study, we found that lovastatin dysregulated lysine succinylation of cytoskeleton-associated proteins in CSCs derived from TNBC MDA-MB-231 cell. Lovastatin inhibited EMT as demonstrated by down-regulation of the protein levels of Vimentin and Twist in MDA-MB-231 CSCs in vitro and vivo and by reversal of TGF-β1-induced morphological change in MCF10A cells. Combination of lovastatin with doxorubicin synergistically inhibited liver metastasis of MDA-MB-231 CSCs. Lovastatin also inhibited the migration of MDA-MB-231 CSCs. The disruption of cytoskeleton in TNBC CSCs by lovastatin was demonstrated by the reduction of the number of pseudopodia and the relocation of F-actin cytoskeleton. Bioinformatics analysis revealed that higher expression levels of cytoskeleton-associated genes were characteristic of TNBC and predicted poorer overall survival in breast cancer patients. These data suggested that lovastatin could inhibit the EMT and metastasis of TNBC CSCs in vitro and in vivo through dysregulation of cytoskeleton-associated proteins.